TEACHING RECOUNT TEXT WRITING THROUGH THE USE OF PARALLEL WRITING TECHNIQUE TO THE FOURTH SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT, NUSA CENDANA UNIVERSITY, KUPANG, NTT - Liunokas Yanpitherszon (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
This research deals with the students’ ability in writing descriptive text through outdoor learning activity at the sixth semester of English language education study program of Palopo Cokroaminoto University. The population of this research is the Fourth Semester Students of English Education Department, Nusa Cendana University, Kupang, NTT. Writing test is the instrument of this research. Based on the findings and discussion.  Based on the findings and discussion, the researcher concludes that the use of parallel writing technique is effective in developing students’ vocabulary in writing at the Fourth Semester Students of English Education Department, Nusa Cendana University, Kupang, NTT.  It was proven by there was a significant difference between the students’ mean score of pretest and posttest. In pretest, the students’ mean score is 26 and the students’ score in posttest is 51. In addition, the result of statistical analysis for level of significance (p=0.05). The probability value was smaller than α (0.00<0.05). it indicated that there is significant differences between the result of pre-test and post-test after giving treatment in building students’ vocabulary in writing by applying parallel writing technique to the Fourth Semester Students of English Education Department, Nusa Cendana University, Kupang, NTT.